The impact of challenge and hindrance stressors on knowledge hiding: the mediating role of job crafting and work withdrawal - Wang, Le; Jia, Yongtang; Xie, Kun (Frontiers in Psychology, 2024)
The purpose of this study is to explore the impact of challenge and hindrance stressors on employees' knowledge-hiding behavior, based on self-reported data from 493 Chinese preschool teachers. The findings indicate that both challenge and hindrance stressors significantly increase knowledge hiding, with hindrance stressors exerting a more pronounced effect. Furthermore, the study reveals the mediating roles of job crafting and work withdrawal, highlighting the distinct mechanisms involved with these stressors. Specifically, challenge stressors increase the likelihood of knowledge hiding through work withdrawal while simultaneously decreasing it through job crafting; notably, the former pathway has a greater effect. In contrast, hindrance stressors consistently exert detrimental effects, amplifying the probability of knowledge hiding through both mediators, which explains their stronger impact compared to challenge stressors. Additionally, empowering leadership plays a crucial moderating role in this relationship. The adverse influence of hindrance stressors on knowledge hiding, as mediated by job crafting, intensifies under high levels of empowering leadership. These findings not only validate the newly constructed parallel mediation model within an educational context but also provide practical strategies for kindergarten administrators regarding knowledge management. Such strategies include effectively distinguishing and managing different types of job stressors, enhancing skills to empower employees, and organizing regular knowledge-sharing activities.